Faktor-faktor yang Mempengaruhi Kejadian Penyakit Diare di Desa Hutanopan Kecamatan Halongonan Kabupaten Padang Lawas Utara Tahun 2018 - Siregar, Srianty; Batubara, Novita Sari (Universitas Aufa Royhan, 2019)
Diarrheal disease is still the second cause of morbidity and mortality in children aged less than two years. The purpose of this study is to determine the factors that affect the incidence of diarrheal diseases in the village Hutanopan Halongonan District South Tapanuli regency. Population amounted to 400 people with the technique of sampling using simple random sampling with the number of 80 respondents. Methods The study used observational analytics with the test used is Chi-Square test. Based on the results of the study, it is known that the incidence of diarrhea in the village of Hutanopan in the last month as many as 22 people (27.5%). Based on result of calculation which have been done with spss program using chi-square test there is relation between clean water facility with diarrhea occurrence, with P Value = 0,036 There is relationship between latrine ownership with diarrhea occurrence with P value 0,015. There is a relationship of waste Management with the incidence of diarrhea with the value of P Value = 0.026 and there is a relationship of waste water management with the incidence of diarrhea in infants with a value of P value 0.012. It is advisable for the public to advocate further improving basic sanitation including clean water supply, latrine ownership, waste management and wastewater management, especially in the case of garbage disposal whereby the community should have a closed and strong waste bin.